Wat dateer ons? Enkele opmerkings rondom die datering van Bybelse tekste - Lombaard, Christo (HTS teologiese studies, 2002)
What are we dating? Some remarks on the dating of biblical textsWhen a date is ascribed to a Biblical text, it is at times unclear precisely what is being dated. Does the date relate so some historical event which may have occurred, or alternatively, is it projected into another era? Does it refer to the possible formation date of an oral tradition, or is it perhaps some phase in its development through history which is being dated? Is it the a quo date for when a text is judged to have been written down, or the date ad quem, or some process of rewriting – either between these two dates, or possibly some minor editorial alteration after the ad quo date – which is to be given? Is it referring to a time when an interpretative frame was placed around existing text? This article provides an overview of what it is about a text that may be dated. It concludes with an appeal for greater accuracy of formulation in the already precarious matter of dating biblical texts.